Controle lito-estrutural e caracterização aerogeofísica do complexo alcalino Planalto da Serra - Zaffari, Gabriel Luiz (2016)
The Complexo Alcalino Planalto da Serra, is located between the counties of Planalto da Serra and Nova Brasilândia, at the Mato Grosso south-central region among an area of approximately 30 km2. Geologically is inserted in the Neoproterozoic metasediments of the Grupo Cuiabá, and it is composed of alkaline ultramafic rocks such peridotites, pyroxenites, carbonatites and apatitites such the alkaline bodies are plugs and swarm of dikes. The first studies in the CAPS indicated that the alkaline intrusions were Cretaceous and were to alkaline magmatism occurring in lineament 125 °. However, recent geochronological studies, by the methods Rb / Sr, Sm / Nd and Ar/Ar concluded that the age of the complex is about 600 Ma, indicating that the intrusion don’t below at the intrusion model occurring on the Bacia do Paraná border. In order to understand the relationship between the alkaline rocks with metasediments rocks of the Grupo Cuiabá, both in temporal relationship, was executed a geological mapping with lithostructural characterization with focus on the alkaline rocks and their wall rocks, creating regional maps and detail maps, besides profiles and schemes from the those intrusions. Another tool used was the geophysics by gama spectrometry and magnetometry because this methods generates a lot of information for regionally geological mapping. The magnetometry show a big difference between the wall rocks and alkaline rock, being possible to mapping 7 anomalies related to intrusions, being that 3 of them are new alkaline bodies. All these anomalies have high values of nT/m in ASA maps, being possible delimit bodies’ locations. The gamma spectrometry was also used to observe the interference of the alkaline bodies on the surface and as a tool in geological mapping. The alkaline occurrences modify the potassium concentrations in the areas of occurrence, generating a low counting of this element. Features such as deformation and mineral reorientation present in the edges of the alkaline dykes, corroborates with an intrusion model that occurred at a moment syn to tardi-tectonic. The relationship between age and the structural characteristics, deformation and metamorphic brings us to the same orogenic event that affected the rocks of Paraguay Belt.